Unsafe words : queering consent in the #MeToo era - Buggs, Shantel Gabrieal; Hoppe, Trevor, 1983- (Q public, 2023)
"What can the #MeToo moment teach queers about consent? And what can queers teach the rest of the world about ethical sex? This radical book brings together academics, activists, artists, and sex workers to tackle dangerous questions about sex, power, consent, and harm.While the authors in this volume are committed to promoting consensual, pleasurable sex, we reject heteronormative, one-size-fits-all models of consent and sexual ethics.#MeToo ushered in an era of reckoning and accountability for one powerful man after another. But too often it has defined sex and harm in starkly heterosexual-and often white and wealthy-terms."Unsafe Words" tells a queerer side of the #MeToo story. Not all of us seek safety in sex. Nor do we all believe "enthusiastic" models of consent are practical or appropriate for some queer communities. We look instead to the tools queer communities have developed themselves to practice ethical sex-from the sex worker negotiating with her client to the gay man having anonymous sex in the backroom. We also consider how queers can better respond to sexual violence. How can our communities do better at responding to and preventing sexual violence?This challenge is especially daunting in a world where the only recourse made available is typically law enforcement, a pillar of American racism, transmisogyny, and homophobia.How can our communities imagine different responses to sexual violence that do not depend on the law to serve justice?The "unsafe words" in this volume challenge dogmatic assumptions about sex and consent while exploring tools and language to promote better, more ethical, and more pleasurable sex for everyone"--